Special papersChronic total occlusion in ostium of right coronary artery – retrograde approach as the first-choice method of revascularization? - Bryniarski, Leszek; Kameczura, Tomasz; Surowiec, Sławomir; Januś, Bogdan; Derlaga, Bogusław; Dudek, Dariusz; Czarnecka, Danuta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Recanalization of chronic total occlusion (CTO) located in the ostium may require the operator’s ability to use the retrograde approach. We present a case of opening a chronically occluded right coronary artery (RCA) by the retrograde approach after an unsuccessful attempt of recanalization by classic antegrade technique.